Group Guidance Based on Gayo Ethnics’ Cultural Values to Improve Students’ Islamic Characters - Abdi, Sofyan; Sugiharto, Dwi Yuwono Puji; Anwar Sutoyo, Anwar Sutoyo (Jurnal Bimbingan Konseling, 2019)
This study aims to find out the effectiveness of group guidance based on Gayo ethnic’s cultural value to develop the students’ Islamic character. This research used a psychological scale of Islamic character which was consisted of 3 kinds: Iman, Islam, and Ihsan. The research was done in Senior High School 4 Takengon with ten students as the research subjects. The design used is one group pre-test – post-test design. The Wilcoxon data analysis showed the group guidance based on Gayo ethnics’ cultural values was effective to improve students’ Islamic character. The result showed students’ Islamic character level improved after being given the service. Group guidance was done by internalizing Gayo ethnics’ cultural value in every step of the service.